1999
DOI: 10.1016/s0960-9822(99)80136-5
|View full text |Cite
|
Sign up to set email alerts
|

Movement of nuclear poly(A) RNA throughout the interchromatin space in living cells

Abstract: Poly(A) RNA can move freely throughout the interchromatin space of the nucleus with properties characteristic of diffusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
134
4
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 28 publications
16
134
4
1
Order By: Relevance
“…Indeed, recent measurements of the movement of caged¯uorescein-labelled oligo(dT) hybridized to poly(A) RNA in the nucleus, demonstrated that after a photolytic unmasking of the probe, the oligo(dT)-poly(A) RNA hybrids moved at solution rates. In addition, the same apparent diffusion coef®cient was measured for the movement at both 23 8C and 37 8C (Politz et al 1999). It follows that newly synthesized polyadenylated RNAs would diffuse randomly in the nucleoplasm until they reach the NPCs.…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, recent measurements of the movement of caged¯uorescein-labelled oligo(dT) hybridized to poly(A) RNA in the nucleus, demonstrated that after a photolytic unmasking of the probe, the oligo(dT)-poly(A) RNA hybrids moved at solution rates. In addition, the same apparent diffusion coef®cient was measured for the movement at both 23 8C and 37 8C (Politz et al 1999). It follows that newly synthesized polyadenylated RNAs would diffuse randomly in the nucleoplasm until they reach the NPCs.…”
Section: Discussionmentioning
confidence: 61%
“…These findings point to the possible existence of the energydependent step, which is irreversible. Because microinjected RNAs accumulate around the speckles even at 4°C, we infer that the movement of RNAs consists of two steps: the movement of pre-mRNAs toward the speckles is probably the diffusion process (Politz et al, 1999) and their targeting within the speckles is likely an energy-dependent process.…”
Section: Discussionmentioning
confidence: 95%
“…Much of the fluorescence label was found adjacent to the speckles, usually in the form of distinct dots. These results indicate that the movement of pre-mRNA within the interchromatin space toward the speckles was possibly a diffusion process (Politz et al, 1999), but the targeting inside the speckles themselves was temperature-dependent. The results of the experiments in which we microinjected the Ad1 RNA labeled with red fluorochrome and after 15 min of incubation at 37°C microinjected the same cells with the Ad1 RNA labeled with green fluorochrome and incubated for 30 min at 4°C supported this view ( Figure 2D).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…However, Tel15q TERRA clusters display D between 0.15 and 1 × 10 −3 µm 2 /sec (mean D = 0.02 µm 2 /sec), with similar diffusion coefficients observed in both clones (Figure 2E). Compared to previously imaged nuclear mRNAs [34,35], the size and dynamics of TERRA foci suggest that the small particles correspond to single Tel15q TERRA molecules, while the large foci represent clusters of several Tel15q TERRA molecules (supplementary movie 1 and 2).…”
Section: Resultsmentioning
confidence: 76%